2014
DOI: 10.1159/000438921
|View full text |Cite
|
Sign up to set email alerts
|

Response of Adipose Tissue-Derived Stromal Cells in Tissue-Related O<sub>2</sub> Microenvironment to Short-Term Hypoxic Stress

Abstract: A microenvironment low in O2 (‘physiological' hypoxia) governs the functions of perivascular multipotent mesenchymal stromal cells, defining their involvement in tissue physiological homeostasis and regenerative remodelling. Acute hypoxic stress is considered as one of the important factors inducing tissue damage. Here, we evaluate the influence of short-term hypoxia (1% O2 for 24 h) on perivascular adipose tissue-derived cells (ASCs) permanently expanded in tissue-related O2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
(49 reference statements)
2
9
0
Order By: Relevance
“…Firstly, the increased level of intracellular ROS at 0.1% O 2 may enhance the activity of ASC antioxidant systems. Previously, we demonstrated mild oxidative stress followed by an increase in superoxide dismutase activity in ASCs cultured continuously under 5% O 2 [38, 45]. Secondly, the downregulation of TP53 (p53), FASLG (Fas ligand), and APC gene expression and upregulation of SFN (14-3-3 sigma) expression found in this study should prevent apoptotic events.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Firstly, the increased level of intracellular ROS at 0.1% O 2 may enhance the activity of ASC antioxidant systems. Previously, we demonstrated mild oxidative stress followed by an increase in superoxide dismutase activity in ASCs cultured continuously under 5% O 2 [38, 45]. Secondly, the downregulation of TP53 (p53), FASLG (Fas ligand), and APC gene expression and upregulation of SFN (14-3-3 sigma) expression found in this study should prevent apoptotic events.…”
Section: Discussionsupporting
confidence: 59%
“…Numerous studies of various cell types have shown that HIF-1 α stabilisation has a considerable effect on RhoA activity, which is followed by changes in migration activity [22, 23, 60]. We have previously demonstrated changes in the expression of HIF family transcription factors in tissue O 2 -adapted ASCs after hypoxic stress [45]. Particularly, statistically significant downregulation of HIF-1α and upregulation of HIF-3α expression in ASCs were found 24 h after hypoxic (1% O 2 ) exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further study revealed an attenuation of targeted and non-targeted migration of ASCs after O 2 deprivation (Udartseva et al, 2016). These data appeared to be quite surprising as earlier acute hypoxic exposure of ambient (20%) O 2 -adapted MSCs was shown to enhance migration rate (Buravkova et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, we were the first to describe ASC “on site” response on acute hypoxic stress. We successfully demonstrated that tissue O 2 ‐adapted ASCs are resistant to short‐term hypoxia, which can ensure their effective involvement in the regeneration of tissue damage under significant oxygen deprivation (Andreeva, Lobanova, Udartseva, & Buravkova, ). Further study revealed an attenuation of targeted and non‐targeted migration of ASCs after O 2 deprivation (Udartseva et al, ).…”
Section: Discussionmentioning
confidence: 99%